A STEMI mimic (Brugada ECG pattern) unveiled by influenza fever. Issue 5 (2nd September 2020) - Kaur, Parminder; Bendaram, Snigdha Reddy; Singh, Balraj; Elkattawy, Sherif; Sah, Anuraag; Noori, Muhammad; Pullatt, Raja; Shamoon, Fayez
ABSTRACT: Brugada syndrome is a genetic disease with a characteristic electrocardiogram (ECG) findings of ST elevation in leads V1–V3 with a right bundle branch block (RBBB) appearance called Brugada ECG pattern and a tendency to develop malignant polymorphic ventricular arrhythmias that may lead to syncope or cardiac arrest. Common triggers for Brugada ECG pattern include fever, tricyclic antidepressants, lithium, cocaine and alcohol. This ECG pattern together with clinical findings mentioned above is termed Brugada Syndrome. We report a case of a 51-year-old male with a past medical history of hypertension presented to emergency department with 2-day complaint of fever, chills, sore throat, nasal congestion, malaise, productive cough, was positive for Influenza B and on ECG found to have type-I (coved) Brugada ECG pattern. Influenza fever associated with Brugada ECG pattern is a rare manifestation; in fact, to the best of our knowledge, only three case reports have been published in the literature to date.